What do users want? An analysis of enquiries received at the Help Desk - Goh, Wei Haan *; Sinnasamy, Janaki * (2016)
Librarians are expected to equip themselves with knowledge of the various information resources available and tips for efficient search strategies before being given the task of helping out at the Help Desk. For this reason, fresh librarian are often paired with senior librarians when on duty. However, the emergence of multitude online resources and the inherent digital skills of the Net generation seem to have a shrinking effect on the need for academic related types of enquiries. The objective of this paper is to analyse and study the characteristics and changes in the trends of reference enquiries received at the Help Desk particularly in the Sunway Campus Library. All enquiries received either in person, phone, email or via social media are recorded in the Reference Enquiries Database developed by the Automation division. Enquiries received are categorised as Simple or In-Depth enquiries. The Simple enquiries are categorised as; Bibliograph instruction, Directional Questions, Computer & IT related; nformational, and Others. In-depth enquiries consist of Literature Search and Bibliographical Verification. This paper will plot the types of enquiries received for 3 years (2014-2016) and analyse the changes and trends in the types of enquiries received. It is hoped that this analysis will give an insight to the changing needs of library users and help academic libraries to plan, modify, and re-evaluate Help Desk services.